Secondary curriculum policy statement - Belize. Ministry of Education. Curriculum Development Unit (Ministry of Education, 1991)
This policy statement for the secondary school curriculum in Belize addresses five areas: 1) Basic conceptualization, 2) The core curriculum and its options, 3) The whole school curriculum, 4) Staff development programmes, and 5) The role of the Education Officer (Secondary Curriculum).
Keywords: Secondary school curriculum